Physics Learning Using Guided Inquiry Models Based on Virtual Laboratories and Real Laboratories to Improve Learning - simbolon, dedi holden; Silalahi, Eka Kartika (Journal for Lesson and Learning Studies, 2023)
The lack of teacher creativity in testing various learning models and methods makes a significant contribution to the stigma of boredom and boredom in studying physics. The right learning model is needed so that it can help students improve learning outcomes, especially learning physics. The purpose of this study was to analyze the influence the experimental method combined with the virtual and real experiment-based guided inquiry learning model had on the physics learning outcomes. The research samples were class XI IPA 1 (32 people) for the experimental group and class XI IPA 2 (32 people) for the control group. In this study, the cluster sampling technique used was random sampling. Data collection techniques in research are in the form of learning outcomes test instruments at the beginning (pretest) and at the end of learning (posttest). The data analysis technique used is the normality test and the independent sample t-test. To test the research hypothesis, two similarity tests were used on average using the t test, namely the independent sample t-test or one-way analysis of variance (ANOVA) using the SPSS version 21 program. The result show that the guided inquiry learning model uses virtual laboratories and real laboratories to influence student learning outcomes (0.000 < 0.05). Based on the research results, it can be concluded that virtual and real experiments can improve students' physics learning outcomes, as evidenced by the difference in the average score of students' learning outcomes in the experimental class (87.47) compared to the control class (69.72).